PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI FINANSIAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DI RSIA MUTIARA BUNDA - Supriatin; Wimby Wandary (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
The aim of this research is to analyze the influence of transformational leadership, compensation financial and commitment organization towards employee performace at RSIA Mutiara Bunda. The population of this research is all 86 active employees at RSIA Mutiara Bunda. Saturation Sampling technique was used to determine the sample. Data is analyzed using multiple linear regression analysis. Based on the analysis, it can be concluded that: (a) Transformational leadershid gives negative impact upon employee performance. (b) Compensation financial brings positive influence upon employee performance (c) commitment organization brings positive influence upon employee performance (d) transformational leadership, compensation financial and commitment organization significantly influence employee performance.